2018
DOI: 10.1002/jcp.27920
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐10 responses from acute exercise in healthy subjects: A systematic review

Abstract: Purpose Interleukin 10 (IL‐10) is a cytokine that plays a critical role with potent anti‐inflammatory properties when produced during exercise, limiting host immune response to pathogens and preventing tissue damage. The purpose of this systematic review was to assess the response of IL‐10 after acute exercise session in healthy adults. Methods Databases of Ovid Medline (1978–2016), CINAHL (1998–2016), EMBASE (2003–2016), SportDiscus (1990–2016), and Web of Science library (1990–2016) were carefully screened. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 33 publications
5
44
0
Order By: Relevance
“…Previous studies suggested that the effect of aerobic exercise on the cytokines' increase is different from the effect of strength/resistance exercise, with the latter being less evident (Santos et al, 2019). This is in line with our evidence.…”
Section: Implications For Practicesupporting
confidence: 93%
See 1 more Smart Citation
“…Previous studies suggested that the effect of aerobic exercise on the cytokines' increase is different from the effect of strength/resistance exercise, with the latter being less evident (Santos et al, 2019). This is in line with our evidence.…”
Section: Implications For Practicesupporting
confidence: 93%
“…Regardless, levels of IL-10 tend to peak during recovery time from exercise, with the magnitude of the increase being related to the active muscle mass and exercise intensity. Overall, the duration of the exercise was the most important factor determining the magnitude of the exercise-induced increase of plasma IL-10, as recently reviewed by Santos et al (2019). This increase in IL-10 could be related to the prevention of potential deleterious chronic low-grade inflammation and tissue damage.…”
Section: Exercise-induced Effects On Cytokinesmentioning
confidence: 95%
“…Thus, the exercise appears to be a low‐cost alternative to improve obesity‐related inflammatory disorders by increasing concentrations of IL‐10 and IL‐33. Confirming this, a recent systematic review highlighted the role of exercise for the increase of systemic IL‐10 levels . Here, a 1 week HIIT was able to increase the peripheral frequency of Treg and mTreg cells in obese individuals.…”
Section: Discussionmentioning
confidence: 99%
“…They may be useful markers for assessing the effects of physical exercise on the immune system. For instance, cytokine IL-6 augments anti-inflammatory cytokines (such as IL-10), which exhibit potent anti-inflammatory properties when produced during exercise [18], blocking a possible persistent inflammatory state while stimulating the production of interleukin-1 receptor antagonist (IL-1ra) [19].…”
Section: Discussionmentioning
confidence: 99%